Meaning of diabetes mellitus among Chontal Indigenous people of Tabasco, Mexico. - Cruz-Sánchez, Marcelina (2020)
Background: Diabetes Mellitus (DM) is a growing public health problem and indigenous populations are no exception. Although the problem has been studied from different perspectives, little has been investigated about the meaning it has for this population; Objective: To understand the meaning of Diabetes and some gender differences in indigenous Chontales. Methodology: A qualitative study was carried out with 29 people aged 20 years and over, selected from the registry of the health center; the in-depth interview was used, prior consent was audio-recorded; the analysis was carried out through transcription, coding, segmentation, reduction and interpretation of the discourses produced. Results: 29 informants participated, 21 women; average age was 48.5 years; All married; 100% women were engaged in unpaid domestic work; the predominant schooling was primary (six years or less). DM was signified as a fatal fate; distrust was found in the dialysis and insulin treatments, meant as precursors of death. Herbalism is used and signified as an effective treatment for Diabetes; According to the informants, it is women who carry out the self-care of the disease the most; Lastly, significant trust in God was found for health outcomes. Conclusions: Diabetes is meant as a death sentence; Dialysis and insulin are meanings as procedures that accelerate death, this suggests to health care providers to consider the meanings of the disease and incorporate interculturality in the care of indigenous people.